2011
DOI: 10.3844/ajassp.2011.1107.1115
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dispositional Factors and Work-Family Conflict on Job Satisfaction among Single Mother Employees

Abstract: Problem statement: Few studies have tested the indirect effects of dispositional factors including perfectionism and locus of control on job satisfaction through work-family conflict. Approach: This study examined the indirect effects of perfectionism and locus of control on job satisfaction through work-family conflict. The sample consisted of 159 single mother employees. Data were gathered using self-administered questionnaires. The data were analyzed using structural equation modeling procedure to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Studies on the interface between work and family roles have the tendency to focus on the negative side of the interface, that is work-family conflict and studies on the positive side of work-family interface are relatively lacking (Brough and Kalliath, 2009;Aminah and Noryati, 2011). However, there have been a growing number of researchers who have recognized the positive side of this interface (Greenhaus and Powell, 2006;Noraani et al, 2011;Wayne et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the interface between work and family roles have the tendency to focus on the negative side of the interface, that is work-family conflict and studies on the positive side of work-family interface are relatively lacking (Brough and Kalliath, 2009;Aminah and Noryati, 2011). However, there have been a growing number of researchers who have recognized the positive side of this interface (Greenhaus and Powell, 2006;Noraani et al, 2011;Wayne et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One study also examined substance‐use outcomes such as for alcohol and cigarettes (Frone et al, ). Nine studies reported significant inverse associations between WFC and work‐related outcomes such as job satisfaction, task enjoyment, work commitment, and work engagement (Ahmad, ; Ahmad et al, ; Ahmad & Ngah, ; Casper et al, ; McManus et al, ; Mulvaney et al, ; Noor, ; Opie & Henn, ; Williams et al, ). Six studies examined reported significant, inverse relationships between WFC and non‐work‐related or family‐related outcomes, such as parent–child interaction, parent averseness parenting warmth, couple relationships quality, adolescence sleep quality and physical health (Ahmad, ; Almeida & Davis, ; Bull & Mittelmark, ; Cooklin et al, ; Frone et al, ; Lawson et al, ; Repetti & Wood, ) and one study a positive association between WFC and child negative affect (Repetti & Wood, ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, McManus et al () compared a total of 178 mothers (89 sole and 89 partnered) in one study and 72 mothers (36 sole and 36 partnered) in another study. For studies including only sole mothers, the smallest size was 159 mothers for two of the studies (Ahmad et al, ; Ahmad & Ngah, ). Third, all but three studies were cross‐sectional, with only Killien et al (), Mulvaney et al (), and McManus et al () adopting longitudinal designs.…”
Section: Limitations Of Previous Studiesmentioning
confidence: 99%
“…Personality factors often influence how individuals perceive their situation or environment and as a result this perception will affect the outcome of work-family relationships. Several studies have found that dispositional factors, individual differences or personality characteristics are related to WFC or WFE experiences (Ahmad & Ngah, 2011;Allen et al, 2012;Baral & Bhargava, 2011a). Allen et al (2012) conducted a meta-analysis on the relationship between dispositional variables and WFC, and suggested to examine the relationship between dispositional variables and the positive side of workfamily relationships.…”
Section: Optimism and Wfementioning
confidence: 99%